Brain-Mind-Body Practice and Health - Gangyan Si (Frontiers Research Topics, 2018)
It is acknowledged that practice could induce rapid change or reorganization of the brain's cellular or neural networks as well as behaviors. Notably, practice relevant to mental or physical approach attracted great attention in this decade. It highlights profound significance both for human evolvement and individual development. Specifically, acquiring fine motor skills is a crucial premise for human being to evolve to modern human by using tools in one side. In the other side, numerous evidences indicated that motor learning involved in limb and trunks promotes the development of individual brain in anatomy and functions. Hence, motor learning is also tightly associated with developmental plasticity. These studies on brain-mind-body practice illuminate a promising way in promoting human brain health. This editorial covers wide range of brain-mind-body practice forms to summarize recent new findings and development from behavioral, physiological, neurobiological and psychological science approaches. In this research topic, we addressed recent findings from theoretical as well as experimental perspective including contributions under the following three headings: 1) intervention studies to investigate the positive effect of brain-mind-body practice on cognition and relevant brain mechanism. The intervention pattern consisted of short-term practice ranging from few hours to several weeks; 2) cross-sectional studies using expert-novice paradigm to explore the behavioral and neural system change induced by extensive brain-mind-body practice; 3) the mediators influence the relationship between practice and health outcomes and 4) new viewpoints on brain-mind-body practice from theoretical perspectives. Here we briefly highlight these articles aiming to provide a deep understanding for the association between practice, plasticity and health for readers. Additionally, it offers new insights for developing possible practice interventions for clinical treatment of neurological dysfunction or disorders.